Pengaruh Tekhnik Pernafasan Buteyko Terhadap Fungsi Ventilasi Oksigenasi Paru - Muhammad Arif; Mariza Elvira (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2018)
Patients suffering from asthmadevelop bronchospasm and bronchokontriksi resulting in hyperventilation resulting in decreased ventilation and oxygenation. Interventions to maintain lung oxygenation ventilation function one of them with Buteyko respiratory technique intervention. The purpose of this study was to identify the effect of Buteyko respiratory technique on lung oxygenation ventilation function in bronchial asthma patients. The research design used quasy experiment nonequivalent pre-post control group, and sample number of both groups respectively 15 respondents.The intervention group performed Buteyko breathing technique for 6 weeks.Sampling by consecutive sampling technique. The results of this study indicated that there was a significant difference in pulmonary oxygen ventilation function after Buteyko's breathing technique for 6 weeks (p = 0.00, α = 0.05). The researcher's recommendation is to improve the ventilation function of lung oxygenation by intervening Buteyko respiratory technique in bronchial asthma patient